2005
DOI: 10.2337/diabetes.54.7.2117
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Processing of Human Proislet Amyloid Polypeptide Results in Increased Amyloid Formation

Abstract: The amyloid present in the islets of Langerhans in type 2 diabetes is polymerized islet amyloid polypeptide (IAPP). The precursor protein proIAPP is posttranslationally modified, a process involving the removal of NH 2 -and COOH-terminal flanking peptides. This step is performed by the prohormone convertases PC2 and PC1/3. PC2 processes proIAPP preferably at the NH 2 -terminal processing site, and PC1/3 processes proIAPP exclusively at the COOH-terminal site. Little is known regarding the exact circumstances l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 55 publications
5
96
0
Order By: Relevance
“…Enhanced prohIAPP processing in exenatide-treated human islets is associated with reduced amyloid formation during culture Impaired prohIAPP processing at its NH 2 -terminus has been shown to contribute to amyloid formation [30,31]. Therefore, we examined whether improved prohIAPP processing in exenatide-treated human islets can decrease formation of hIAPP aggregates, thereby reducing amyloid beta cell toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Enhanced prohIAPP processing in exenatide-treated human islets is associated with reduced amyloid formation during culture Impaired prohIAPP processing at its NH 2 -terminus has been shown to contribute to amyloid formation [30,31]. Therefore, we examined whether improved prohIAPP processing in exenatide-treated human islets can decrease formation of hIAPP aggregates, thereby reducing amyloid beta cell toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…However, our studies suggest that exenatidetreated human islets release mainly mature hIAPP rather than immature (pro)hIAPP. Accordingly, previous studies have shown that an elevated hIAPP level per se, such as its overexpression in hIAPP-expressing mice, is not sufficient for amyloid formation [46] whereas elevated production and release of immature (pro)hIAPP potentiates hIAPP aggregation [30,31]. Importantly, improved prohIAPP processing by enhancing beta cell function in human islets with exenatide was associated with a lower number of islets containing hIAPP oligomers and amyloid deposits as well as a lower islet amyloid area in relation to total islet area compared with non-treated cultured islets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of human proIAPP in PC1/3-and PC2-deficient cell lines promotes increased amyloid deposition and apoptosis [28]. We have previously demonstrated that cultured human proIAPP-overexpressing islets lacking PC2 develop increased amyloid formation and cell apoptosis compared with islets with normal PC2 levels [29].…”
Section: Introductionmentioning
confidence: 99%